Biochemical studies on the role of the XPF-ERCC1 endonuclease in repairing damaged DNA replication forks - Abdullah, U (2015)
The human XPF (ERCC4) and ERCC1 proteins form a heterodimeric endonuclease that plays a critical role in maintaining genome stability. Mutations in the XPF gene cause several heritable disorders including Fanconi anemia (FA). This highlights the importance of DNA repair processes controlled by XPF-ERCC1, including the repair at replication forks stalled by DNA interstrand crosslinks (ICLs), for human health. Unrepaired ICLs, formed by by-products of cellular metabolism, are believed to be responsible for the genomic instability, cellular attrition and cancer predisposition seen in FA patients. Additionally, ICL-inducing agents are extensively utilised in anti-cancer therapy. Previous reports suggest that ICL processing is triggered when the leading strand of a replication fork collides with an ICL, where XPF-ERCC1 catalyses fork incisions to initiate a process termed 'ICL unhooking'. However, the mechanism(s) of fork processing by XPF-ERCC1 remain poorly explored. Using biochemical reconstitution, I show that ICL unhooking, the initiating steps of replication-coupled ICL repair, is driven by the collaborative efforts of XPF-ERCC1; the replicative single-stranded DNA binding protein RPA; and the 5' to 3' exonuclease SNM1A. XPF-ERCC1 incises ICL-containing fork structures within the duplex DNA region. However, the presence of a model nascent leading strand, mimicking the effects of replication arrest by ICL, eliminates this activity. Strikingly, addition of RPA restores XPF-ERCC1 activity on such structures. SNM1A is able to load onto XPF-ERCC1-RPA induced incisions and digest past the ICL to unhook the ICL from duplex DNA. I postulate that during replication-coupled ICL repair, the arrest of nascent leading strands by ICLs produces a substrate that is inhibitory to XPF-ERCC1. This inhibition can be overcome through the marked stimulation of XPF-ERCC1 by RPA. XPF-ERCC1-RPA induced-incision enables SNM1A to digest past the ICL, which unhooks the ICL from the duplex DNA, enabling subsequent repair process to occur.